Glossing over cryptic species: Descriptions of four new species of Glossodoris and three new species of Doriprismatica (Nudibranchia: Chromodorididae) - Matsuda, Shayle B.; Gosliner, Terrence M. (Zootaxa, 2018)
Advances in molecular systematics have led to a rapid increase in the identification of cryptic and pseudocryptic species in organisms exhibiting diverse and complex coloration with complicated taxonomic histories. A recent molecular phylogenetic analysis of nudibranchs in the genus Glossodoris (Mollusca: Gastropoda: Heterobranchia: Chromodorididae) and related genera identifies multiple cryptic and pseudocryptic species complexes, one within Glossodoris pallida and three within Glossodoris cincta, and support for three new species of Doriprismatica. Morphological analyses of color pattern, radular structure, buccal mass, and reproductive system support these identifications. Descriptions for Glossodoris buko sp. nov., Glossodoris bonwanga sp. nov., Glossodoris andersonae sp. nov., Glossodoris acosti sp. nov., and what will retain the name Glossodoris sp. cf. cincta are provided here, in addition to descriptions for new species Doriprismatica balut sp. nov., Doriprismatica rossi sp. nov., and Doriprismatica marinae sp. nov.. Glossodoris pallida and G. buko exhibit extreme differences in radular structure in addition to a clear biogeographic split in range. Glossodoris bonwanga, G. andersonae, G. acosti and G. sp. cf. cincta, share morphological and geographic differences but these are not as pronounced as in G. pallida and G. buko. More detailed study of the G. cincta complex is necessary to resolve some remaining systematic challenges. Doriprismatica balut is clearly distinct from all other congeners based on molecular and morphological characters. In contrast, D. rossi and D. marinae are not strongly divergent genetically, but have major morphological divergences that clearly distinguish them.